A Framework for Quantum based Software Development Process - Nagarajan, Sathishkumar; Malarvel, Muthukumaran; J, Thangakumar (2024 International Conference on Advances in Data Engineering and Intelligent Computing Systems (ADICS), 2024)
Quantum software is essential for fully harnessing the capabilities of quantum computing systems. Consequently, it has been garnering growing interest in recent times. This document provides a precise definition of the concept of "quantum software engineering" and presents a comprehensive framework for the life cycle of quantum software. Given the interdisciplinary nature of quantum computing, it is essential to establish a shared understanding of the process for developing and implementing a quantum software application. At present, there isn't a complete methodology or lifecycle that covers every significant stage that could come up along the process of development and execution. That's why we provide the quantum software lifecycle in this document. With this paradigm, practitioners, developers, and scholars have a clear path forward for quantum computing. The provision of a methodical development roadmap for quantum- principles-based software encourages creativity in this quickly expanding subject.